2018
DOI: 10.1037/vio0000074
|View full text |Cite
|
Sign up to set email alerts
|

Substance use and intimate partner violence: A meta-analytic review.

Abstract: Objectives: This meta-analysis examines the strength of the link between substance use (e.g., alcohol use vs. drug use) and intimate partner violence (IPV) perpetration and victimization. Method: Data from 285 studies (yielding 983 effect sizes (ESs) and a combined sample size of 627,726) were analyzed using random effects. Moderator analyses compared the impact of overall substance abuse, alcohol use, and drug use on IPV perpetration and victimization for males and females. Results: Overall substance use, alc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

18
236
1
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 298 publications
(258 citation statements)
references
References 46 publications
18
236
1
3
Order By: Relevance
“…Studies from countries including, Australia, South Africa, Spain, Japan, the USA and Sweden have shown that DAV is a common experience among women with PSU (Ahmadabadi et al, 2019;Watt et al, 2017;Gilchrist et al, 2012;Yoshihama et al, 2010;Hughes et al, 2010;Stene et al, 2012). This was also identified in a meta-analysis by Cafferky et al, (2018) who analysed data from 285 international studies and found that substance use was significantly related to domestic abuse; with illicit drug use showing a stronger correlation to victimisation compared to alcohol. However, the analysis only focused on physical intimate partner violence (IPV), negating the link between PSU and non-physical forms of abuse.…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…Studies from countries including, Australia, South Africa, Spain, Japan, the USA and Sweden have shown that DAV is a common experience among women with PSU (Ahmadabadi et al, 2019;Watt et al, 2017;Gilchrist et al, 2012;Yoshihama et al, 2010;Hughes et al, 2010;Stene et al, 2012). This was also identified in a meta-analysis by Cafferky et al, (2018) who analysed data from 285 international studies and found that substance use was significantly related to domestic abuse; with illicit drug use showing a stronger correlation to victimisation compared to alcohol. However, the analysis only focused on physical intimate partner violence (IPV), negating the link between PSU and non-physical forms of abuse.…”
Section: Introductionmentioning
confidence: 78%
“…However, these figures could be higher than indicated because the APMS, like Cafferky et al's (2018) international meta-analysis, did not account for non-physical forms of abuse. Second, data from the Crime Survey for England and Wales (ONS, 2018) shows that of the 1.3 million women who experienced domestic abuse in the past year, 8.1% were under the influence of alcohol and 1.7% were under the influence of drugs during their most recent experience of abuse (ONS, 2018).…”
Section: Introductionmentioning
confidence: 90%
“…age, gender, socio‐economic status, illicit drug use ). However, meta‐analyses that control for such variables find the association between alcohol use and violence remains significant . A third view is that alcohol use increases aggression through pharmacological effects on executive functioning, such as disinhibition of aggressive impulses .…”
Section: Introductionmentioning
confidence: 89%
“…Meta‐analytic reviews of alcohol use in male‐to‐female and female‐to‐male IPV show evidence of small to moderate effects from alcohol use , similar in magnitude to that of childhood exposure to, or experience of, family violence . Cafferky et al conducted a meta‐analysis on the relationship between substance use and IPV perpetration and victimisation, and found small mean effect sizes for illicit drug use and perpetration ( r = 0.23), illicit drug use and victimisation ( r = 0.23), alcohol use and perpetration ( r = 0.20), and alcohol use and victimisation ( r = 0.17).…”
Section: Introductionmentioning
confidence: 99%
“…Robust evidence supports an association between SU (i.e. alcohol and drug use) and IPV, with a consensus that SU can increase both the frequency and severity of violence (Cafferky et al, 2018;Leonard & Quigley, 2017). Findings have highlighted that rates of physical or sexual violence perpetration among men receiving treatment for SU are far higher than those within the general population O'Farrell et al, 2003;O'Farrell et al, 2004;Taft et al, 2010;Ten Have et al, 2014).…”
Section: Introductionmentioning
confidence: 98%